2021
DOI: 10.1080/08952841.2021.1915685
|View full text |Cite
|
Sign up to set email alerts
|

Social relationships and the importance of community-based fitness programs (CBFP)

Abstract: Identifying opportunities for social interaction is key in addressing those at risk of social isolation. Drawing from focus groups with 55 women over the age of 60, this brief report outlines how this community-based fitness program (CBFP) acts as a conduit for social relationships, fosters a sense of belonging, and has social benefit for both active and passive participants. Study participants expressed feelings of kinship within the routine of scheduled classes and group culture. The need to further explore … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 53 publications
1
6
0
Order By: Relevance
“…The effects of the interventions on social participation, however, were not as obvious (53.3% of quantitative studies reported positive associations). In the qualitative studies, participants reported that involvement in the programs gave them the opportunity to get out and be among other people with similar experiences ( 32 , 35 ), feel more social engagement and social support ( 36 , 37 ), be more socially connected ( 38 , 39 ), and expand their communication beyond the group exercise ( 39 ). In the participants' opinion, physical activity programs also helped them to improve their physical performance in everyday life (e.g., strength, endurance, balance, coordination) ( 32 , 35 , 37 , 39 , 40 ).…”
Section: Resultsmentioning
confidence: 99%
“…The effects of the interventions on social participation, however, were not as obvious (53.3% of quantitative studies reported positive associations). In the qualitative studies, participants reported that involvement in the programs gave them the opportunity to get out and be among other people with similar experiences ( 32 , 35 ), feel more social engagement and social support ( 36 , 37 ), be more socially connected ( 38 , 39 ), and expand their communication beyond the group exercise ( 39 ). In the participants' opinion, physical activity programs also helped them to improve their physical performance in everyday life (e.g., strength, endurance, balance, coordination) ( 32 , 35 , 37 , 39 , 40 ).…”
Section: Resultsmentioning
confidence: 99%
“…The community-based nature of CF and DEF training likely contributed to some of the improvements we observed. In fact, community-based or group fitness programs have been shown to foster a sense of belonging and foster other health benefits ( 24 27 ). The sense of community has been shown to be one of the most appreciated benefits of individuals engaged in CF training ( 11 ).…”
Section: Discussionmentioning
confidence: 99%
“…Literature on the role of social relations in health promotion, the focal area of this report, often highlights the positive aspects of social networks (e.g., Barragan, 2021;Berkmann, 1995;Donev et al, 2008). By combining the aforementioned knowledge of ambivalent social influences on health outcomes with insights from research on health campaigns, we provide a broader picture of how positive and negative social aspects should be considered in health promotion.…”
Section: Social Aspects In Health Promotionmentioning
confidence: 96%